2021
DOI: 10.1177/0018726721989792
|View full text |Cite
|
Sign up to set email alerts
|

Managing liminal time in the fly-in fly-out work camp

Abstract: Fly-in fly-out (FIFO) work camps are built and organized to ensure that long-distance rotational workers are fed, housed, and mobilized in sync with the pressing yet unpredictable rhythms of resource extraction. Positioned thus ‘betwixt and between’ the complex relations of work and life (Johnsen and Sorensen, 2015), the work camp is a generative yet hitherto neglected example of permanent liminality (Bamber et al., 2017) and its temporalities. But what does this mean for workers? If camp does the liminal work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 59 publications
0
27
0
1
Order By: Relevance
“…I reviewed literature on liminality between work and personal systems where some interpret management consultants showing full time availability at all times and all places as being in a state of permanent liminality suspended between work and personal systems (Johnsen and Sørensen, 2015). Others claim that those who regularly experience extended periods of liminality may experience mental health issues (Dorow and Jean, 2021). However, those studying flexible working for management consultants found they were able to manage the tensions between work and personal systems and construct a work life balance (Canibano, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…I reviewed literature on liminality between work and personal systems where some interpret management consultants showing full time availability at all times and all places as being in a state of permanent liminality suspended between work and personal systems (Johnsen and Sørensen, 2015). Others claim that those who regularly experience extended periods of liminality may experience mental health issues (Dorow and Jean, 2021). However, those studying flexible working for management consultants found they were able to manage the tensions between work and personal systems and construct a work life balance (Canibano, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In their study of a work camp based in an oil field, Dorow and Jean (2021) found, much like a consulting engagement, the work camp is a liminal organization with its own internal routines, rhythms, and rules, a temporal liminal space. They found that those required to stay on rotation for two weeks between visits home experienced feelings of monotony, disorientation and entrapment, They also developed an abnormal focus on future goals such as early retirement, and the high pay they received, which they saw as offsetting the sacrifice of family and personal time.…”
Section: Liminality Between Work and Personal Systems Of Engagementmentioning
confidence: 99%
See 3 more Smart Citations